Oral health-related knowledge, practice, and utilization of dental services among pregnant women in Riyadh, Saudi Arabia - Mamata Hebbal; Eman I. AlSagob; Sree Lalita Kotha; Varkey Nadakkavukaran Santhosh; Ram Surath Kumar; Silvia Mertins; Aalia Alharthi; Nada Aljubran; Shrooq Alqhtani (PLoS ONE, 2025)
Background Promoting and maintaining appropriate oral hygiene practices in pregnant women is recommended as an integral component of prenatal care to ensure healthy pregnancies and positive birth outcomes. This study aimed to assess the oral health-related knowledge, practices, and utilization of dental services among pregnant women in Riyadh, Saudi Arabia. Methods A cross-sectional survey of 1120 pregnant women was conducted in both government and private maternal hospitals from October 2022 to January 2023. A self-administered questionnaire was developed and validated, comprising 37 closed-ended questions. Data analysis involved descriptive analysis, Kruskal-Wallis test, and Spearman correlation coefficient. Multiple linear and multivariable logistic regression analyses were carried out using socio-demographic variables as predictors for knowledge, practices, and utilization of dental services. Level of significance was set at P ≤  0.05. Results Majority (37.2%) of the pregnant women were in the 30-34 years age group. The majority had limited oral health knowledge (59.7% very poor, 23.8% poor), and 66.4% had poor oral health practices. Dental service utilization was suboptimal, with 39.6% never seeking dental care during pregnancy. A positive correlation was seen among knowledge, practices, and utilization of dental services. Multiple linear regression revealed that both knowledge and practices scores were significantly associated with education and occupation; and utilization scores with occupation. Conclusion This study highlights the need for enhancing oral health knowledge, practices, and utilization of dental services among pregnant women in Riyadh. Bridging knowledge and access gaps can enhance the oral and overall health outcomes of mothers and their infants.